Increased regulatory T cells in patients with liver cirrhosis correlated with hyperbilirubinemia and predict bacterial complications. Issue 4 (April 2015) - Huang, Chien‐Hao; Jeng, Wen‐Juei; Ho, Yu‐Pin; Teng, Wei; Chen, Wei‐Ting; Chen, Yi‐Cheng; Lin, Shi‐Ming; Chiu, Cheng‐Tang; Sheen, I‐Shyan; Lin, Chun‐Yen
Abstract: Background and Aim: Patients with liver cirrhosis (LC) were regarded as immunocompromised status with high incidence of bacterial infection. Regulatory T cell (Treg cell) is known as an immune suppressor and also plays an important role in patients with sepsis. This paper aims to study the role of Treg cells in patients with liver cirrhosis and their correlations to bacterial complications. Methods: Thirty‐three normal controls (NC) and 82 cirrhotic patients were enrolled for the case‐control study. The Treg cells, defined as CD4 + CD25 + Foxp3 + T cells, in peripheral blood of these patients were evaluated. Results: The percentage of Treg cells increased significantly in patients with liver cirrhosis when compared with normal volunteers. Furthermore, this increase of Treg cells was mainly memory phenotype defined as CD45RO + Treg cells and was significantly correlated with serum bilirubin levels as evaluated by multiple linear regression analysis. In addition, the tumor necrosis factor (TNF)‐α receptor II (TNFRII) expression also significantly increased on Treg cells in these patients. Interestingly, these membranous TNFRII would be shed and released into supernatant. Lastly, this increased percentage of Treg cells in cirrhotic patients correlate well with and predict subsequent bacterial complications. Conclusion: The Treg cells, mainly with memory phenotype and with high TNFRII expression, increased significantly in patients with liver cirrhosis and significantly correlated with the serum bilirubin levels. Furthermore, this increased Treg cells correlate with and predict subsequent bacterial complications in cirrhotic patients.